INFORMATION TECHNOLOGIES, KNOWLEDGE AND INNOVATION IN SMART CITIES: CURRENT AND FUTURE TRENDS FOR MANAGEMENT RESEARCH - Amel ATTOUR; Carine DOMINGUEZ-PERY; Ygal BENDAVID (Systèmes d’information et management, 2021)
According to the UN Department of Economic and Social Affairs (UN, 2018a), between 1950 and 2018, the world’s urban population grew more than four-fold, from an estimated 0.8 billion to 4.2 billion. By 2050, the less developed regions will account for more than 85 per cent of the total world population and over 80 per cent of the world’s urban population.This global urbanization process is expected to continue for several decades as the number and size of cities continue to grow in line with the rising share of city-dwelling populations. All class of urban settlements including cities (500K-1 million people), large cities (5-10 million people) and megacities (more than 10 million people) are increasing in number. To cope with these patterns of urbanization, and effectively respond to critical challenges of city development, there is a need to provide efficient delivery of services for the well-being of citizens. In order to ensure sustainable urban growth and economic development, cities are increasingly using digital and information technologies (ITs) to innovate their services and governance models. In doing so, it gives rise to a new model of city that is commonly referred to as a “smart city.”So far, in the field of management sciences, smart cities have been primarily explored through two main questions: (i) how a city becomes smart and (ii) what strategies are adopted to carry out such a project (Ben Letaifa, 2015). The associated political processes and choices essentially reflect economic, social and societal challenges of which IT is only the support. Consequently, smart city players tend to position themselves on different key questions such as: the choice of data governance emerging from complex ecosystems (Gupta et al., 2020); the nature of the intelligence to be promoted (rational, emotional, collective, participative); the dimensions to be taken into account in the trajectories of smart cities (Camboim et al., 2019); the levels of transparency and control over the choices made when combining algorithms and/or human beings.These key questions underpin the future trends in the development of a smart city, on the one hand; and on the other hand, they open avenues for future research on smart cities. In this editorial we discuss and present the current and future trends of research on smart cities in management science. In section 1 we position smart cities in the current challenging context. In section 2, we present a bibliometric analysis on IT and the smart city. In section 3 we explore three research directions. Finally, by considering the convergence of elements that constitute a smart city, we conclude this editorial and introduce the papers published in this special issue. Finally, we conclude on the convergence of elements that constitute a smart city and introduce the papesr published in this special issue....